Connectedness of Cultural Values and Learning in Primary School - Dwi Alia; Syihabuddin S (Universitas Pendidikan Indonesia (UPI), 2024)
The research is supported by the need to improve the quality of contextualised and relevant learning. In a cultural value-based learning model, students not only learn abstract concepts, but are also able to connect knowledge with real experiences in their cultural context. UPI Tasikmalaya Campus Laboratory Elementary School has a vision and mission that is relevant to the strengthening of cultural values. This research is to identify cultural values that are relevant to the learning process at UPI Tasikmalaya Campus Laboratory Elementary School, and analyse the impact of cultural values integration on character building. Data were collected through document analysis of the curriculum and school programme of SD Laboratorium UPI Tasikmalaya, and through interviews with several teachers and students at the school. The data generated from this study, some cultural values that are relevant in the context of learning include social values, manners, and good habits. The teachers use various methods and media that reflect local culture, such as practical activities and cultural observations, to help students internalise these values. They believe that teaching with cultural themes will improve students' understanding of academic material and make learning more effective. In addition, cultural values are also used as benchmarks to develop students' attitudes and behaviours, and increase their motivation and participation in class.